2009
DOI: 10.1002/adsc.200800501
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO‐tert‐Butyl Nitrite: An Efficient Catalytic System for Aerobic Oxidation of Alcohols

Abstract: A metal-free catalytic system consisting of 2,2,6,6-tetramethylpiperidine N-oxyl (TEMPO) and tert-butyl nitrite has been developed to activate molecular oxygen for the aerobic oxidation of alcohols. A variety of active and non-active alcohols were oxidized to their corresponding carbonyl compounds in high selectivity and yields.Keywords: alcohols; tert-butyl nitrite; molecular oxygen; oxidation; TEMPO; 2,2,6,6-tetramethylpiperidine N-oxyl (TEMPO) Selective oxidation of alcohols is an important reaction in orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(56 citation statements)
references
References 24 publications
3
53
0
Order By: Relevance
“…Semmelhack [25] and He [26] provided twocomponent catalyst systems (TEMPO/CuCl and TEMPO/TBN). Besides, Hoover [27] discussed the mechanism of copper(I)/TEMPO-catalyzed aerobic alcohol oxidation.…”
Section: Aerobic Oxidation Of 2-norbornolmentioning
confidence: 99%
“…Semmelhack [25] and He [26] provided twocomponent catalyst systems (TEMPO/CuCl and TEMPO/TBN). Besides, Hoover [27] discussed the mechanism of copper(I)/TEMPO-catalyzed aerobic alcohol oxidation.…”
Section: Aerobic Oxidation Of 2-norbornolmentioning
confidence: 99%
“…Then, a TEMPO/TBN doublecomponent and sequential bicycle catalyst system was successfully exploited for alcohol oxidations, and even has been applicable to substrates containing acid-sen-sitive functional groups without the need of the toxic halogen source and acid. [10] The TEMPO used could not be recovered, however. On the other hand, Karimi et al developed a heterogeneous catalyst system, consisting of the SBA-15-supported TEMPO/ Bu 4 NBr/NaNO 2 under acidic conditions, allowing the supported TEMPO to be recoverable.…”
Section: Introductionmentioning
confidence: 96%
“…[10] Further research showed that the thermal decomposition of tert-butyl nitrite (TBN) could also be suitable for the aerobic oxidation of active alcohols, although the efficiency was considerably lower compared to the reaction in the presence of H + . [11] However, a high temperature is necessary in these systems to compensate for the kinetic barrier between NO 2 and TEMPO + . Recently, the use of TEMPO as a catalyst to promote the aerobic oxidation of alcohol has been reported.…”
mentioning
confidence: 99%